2022
DOI: 10.1186/s12889-022-12577-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between satellite-detected tropospheric nitrogen dioxide and acute respiratory infections in children under age five in Senegal: spatio-temporal analysis

Abstract: Background There is growing evidence to suggest that exposure to a high concentration of nitrogen dioxide (NO2) can lead to a higher incidence of Acute Respiratory Infections (ARIs) in children; however, such an association remains understudied in Sub-Saharan Africa due to the limited availability of exposure data. This study explored this association by using the satellite-detected tropospheric NO2 concentrations measured by Sentinel-5 Precursor and ARI symptoms in children under age five col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…However, two studies conducted in Congo found air pollution (PM 2.5 , NO 2 , SO 2 ) is linked with prevalence and incidence of respiratory symptoms [ 52 , 53 ]. Another study conducted in Senegal also found a link between NO 2 exposure and incidence of acute respiratory infections after adjusting for relevant cofounders [ 54 ]. Meanwhile, one cross-sectional study in Senegal also found heavy metal exposure is linked with respiratory diseases [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, two studies conducted in Congo found air pollution (PM 2.5 , NO 2 , SO 2 ) is linked with prevalence and incidence of respiratory symptoms [ 52 , 53 ]. Another study conducted in Senegal also found a link between NO 2 exposure and incidence of acute respiratory infections after adjusting for relevant cofounders [ 54 ]. Meanwhile, one cross-sectional study in Senegal also found heavy metal exposure is linked with respiratory diseases [ 55 ].…”
Section: Discussionmentioning
confidence: 99%